Sign language in South Africa: pedagogic approaches, policy developments and new directions - Ganiso, Mirriam Nosiphiwo (Rhodes University, Faculty of Humanities, School of Languages, 2017)
This objective of this thesis is to present and critique sign language-in-education policy and different teaching pedagogies used by teachers in the Eastern and Western Cape Deaf schools. The research was conducted in four Deaf schools in the Eastern and Western Cape Provinces. Data was collected through methods which include interviews, observations and questionnaires. The study results revealed that there was inconsistency of teaching approaches used by teachers in these different schools because some of them lacked knowledge and sign language skills. Additionally, many teachers who are teaching in Deaf schools did not get sign language training. Thus, the study concluded that some teachers lack knowledge of teaching methods. Also Deaf schools' principals and school governing bodies employ teachers who are coming from the mainstream and who are not necessarily aware of Deaf children's needs, forgetting that Deaf learners will struggle without suitable resources. Furthermore, the study concluded that teachers use different teaching approaches, such as Total Communication, Oral Approach, Signed English, Bilingualism, South African Sign Language (SASL) and other means of communication. Deaf learners were also forced to use Oral Communication although some of them were totally deaf. The research showed that Deaf learners and Deaf teacher assistants were not pleased about the way Deaf learners were being taught. Deaf learners complained about teachers, that they lack sign language communication skills and as a result the learners became the interpreters for the teachers. Teachers in turn complained about the curriculum training which was provided for individual and selected teachers. The research also offers a comparative study, in the sense that the development of sign language across different countries from Europe and Africa as well as the United States of America, is included. The thesis furthermore explores the development of SASL CAPS Curriculum in the Western Cape Province, i.e. grade R-3 which began in 2014 as opposed to the Eastern Cape teachers who experienced difficulties due to limited curriculum implementation resources. Therefore, this research suggests that, the Language Task Team which worked on the new CAPS curriculum should have involved Deaf teachers and teachers more generally in their team and decisions. The research sought to find a theoretical or grammatical basis for the development of SASL, while at the same time providing empirical data gathered from the four respective school sites. This data is analysed and presented in the thesis.
Keywords: Deaf -- Education -- South Africa; South African sign language -- Study and teaching; Sign language -- Study and teaching -- South Africa; Sign language -- Grammar